KESADARAN DAN TANGGUNGJAWAB PELESTARIAN LINGKUNGAN MASYARAKAT MUSLIM RAWA PENING KABUPATEN SEMARANG - Ridwan, Benny (INFERENSI, 2013)
This study aims to determine the role of the preservation of the environment and the consciousness and social solidarity in the Rawa Pening Muslim community. The data was collected through observation and interviews with informants around Rawa Pening. In analyzing the data this research applying the Culture Theme Analisis and interpretive methods. The role of the Muslim community for the preservation of the environment seen through the activities âresik-resik rowoâ(pond cleaning), do not throw plastic waste, do not use electric shock and poisons in fishing, changing litter into useful things, regularly breed the fish and do âsedekah rowoâ (pond charity). the solidarity formed through the ârondaâ or the night watch by turns, compassion and helping others, changing conflict into a peace, promoting honesty, and prioritize prayer time.